Oncogenic role of microRNA‐155 in mycosis fungoides: an in vitro and xenograft mouse model study. (1st September 2017) - Moyal, L.; Yehezkel, S.; Gorovitz, B.; Keren, A.; Gilhar, A.; Lubin, I.; Sherman, S.; Hodak, E.
Summary: Background: MicroRNA (miR)‐155 contributes to the proliferation of mycosis fungoides (MF) in vitro and is upregulated in tumours of MF compared with early MF lesions. Objectives: To investigate the contribution of miR‐155 to the cancerous phenotype and drug resistance of MF/Sézary cell lines. Methods: miR‐155 was inhibited in MF cell lines (MyLa and MJ) by transduction of miRZip anti‐miR‐155, and overexpressed in Hut78 cells by transduction of miRVec‐miR‐155; empty plasmids served as controls. Cells were analysed for response to inducers of apoptosis and cell‐cycle arrest, using fluorescence‐activated cell sorting. Transduced MyLa cells were subcutaneously injected into severe combined immunodeficient mice, and tumours were analysed immunohistochemically and for final size. Result: MyLa and MJ cells expressed a high level of miR‐155; Hut78 cells expressed a low level. MF cell lines stably expressing miR‐155 inhibitor showed increased G2/M arrest in response to N ‐p‐tolyl‐2‐(3, 4, 5‐trimethoxyphenyl quinazolin‐4‐amine) (SL111), an inducer of cell‐cycle arrest, followed by increased apoptosis. Additionally, they showed increased apoptosis in response to suberoylanilide hydroxamic acid (SAHA). Tumours formed in mice from injected anti‐miR‐155‐expressing MyLa cells had a significantly lower volume and higher occurrence of apoptosis than controls. Stable overexpression of miR‐155 in Hut78 cells had no effect. Conclusions: Oncogenic miR‐155 appears to contribute to the cancerous phenotype of MyLa and MJ cells, but not of Hut78 cells, by interrupting activation of the G2/M checkpoint in response to SL111, and decreasing apoptosis in response to SL111 and SAHA, thereby facilitating tumour growth. These findings have implications for the potential development of novel therapeutic modalities for MF incorporating miR‐155 inhibitors.